SIMULATION EDUCATION STRATEGIES: BRIDGING THE GAP BETWEEN THEORY AND PRACTICE (European Journal of Interdisciplinary Research and Development, 2024)
Simulation education has emerged as a transformative approach in bridging the gap between theoretical knowledge and real-world application across various fields such as healthcare, aviation, military, and business. This article explores key strategies for effective simulation-based learning, including setting clear objectives, designing realistic scenarios, fostering interprofessional collaboration, and integrating advanced technologies. It also highlights the importance of active participation, reflective practice, regular assessment, and fostering psychological safety. By continuously evolving and incorporating research advancements, simulation education enhances skill development, decision-making, and teamwork, preparing learners for complex real-world challenges.